2020
DOI: 10.1080/02699206.2020.1833369
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric profiles in children with speech sound disorder: Subclinical hearing loss as a potential factor

Abstract: In the present study, hearing sensitivity in children with speech sound disorder (SSD) is scrutinized. Middle ear function (wideband tympanometry and acoustic stapedial reflexes, ASR) and inner ear function (audiometric thresholds in the conventional 1-8 kHz and extended 10-16 kHz high frequency (EHF) range, and distortion product otoacoustic emissions (DPOAEs 2-10 kHz) were investigated. Hearing results were analyzed in relation to speech discrimination of phonemic contrasts (quiet and in noise conditions) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…When investigating the proportions of participants with poor results, the findings show that DPD participants were more often reported having sub-threshold scores for the total score, and the subscale SAP, EAS, and PSS scores. The finding that the subscale environmental and auditory sensitivity differed between the groups, to the disadvantage of the children with DPD, corroborates the findings of hearing-related problems in DPD children that were found by [3]. In that study, subclinical hearing loss was found in 4-5-year-old children with DPD.…”
Section: Differences With Respect To Clinically Significant Difficultiessupporting
confidence: 86%
See 1 more Smart Citation
“…When investigating the proportions of participants with poor results, the findings show that DPD participants were more often reported having sub-threshold scores for the total score, and the subscale SAP, EAS, and PSS scores. The finding that the subscale environmental and auditory sensitivity differed between the groups, to the disadvantage of the children with DPD, corroborates the findings of hearing-related problems in DPD children that were found by [3]. In that study, subclinical hearing loss was found in 4-5-year-old children with DPD.…”
Section: Differences With Respect To Clinically Significant Difficultiessupporting
confidence: 86%
“…DPD and Speech Sound Disorders (SSD) in childhood are often used interchangeably [2][3][4]. However, SSD includes both functional and organic difficulties with the spoken sound system [5].…”
Section: Introductionmentioning
confidence: 99%